Plant expression and characterization of the transmission-blocking vaccine candidate PfGAP50. Issue 1 (December 2015) - Beiss, Veronique; Spiegel, Holger; Boes, Alexander; Scheuermayer, Matthias; Reimann, Andreas; Schillberg, Stefan; Fischer, Rainer
Abstract Background Despite the limited success after decades of intensive research and development efforts, vaccination still represents the most promising strategy to significantly reduce the disease burden in malaria endemic regions. Besides the ultimate goal of inducing sterile protection in vaccinated individuals, the prevention of transmission by so-called transmission blocking vaccines (TBVs) is being regarded as an important feature of an efficient malaria eradication strategy. Recently, Plasmodium falciparum GAP50 (Pf GAP50), a 44.6 kDa transmembrane protein that forms an essential part of the invasion machinery (glideosome) multi-protein complex, has been proposed as novel potential transmission-blocking candidate. Plant-based expression systems combine the advantages of eukaryotic expression with a up-scaling potential and a good product safety profile suitable for vaccine production. In this study we investigated the feasibility to use the transient plant expression to producePf GAP50 suitable for the induction of parasite specific inhibitory antibodies. Results We performed the transient expression of recombinantPf GAP50 inNicotiana benthamiana leaves using endoplasmatic reticulum (ER) and plastid targeting. After IMAC-purification the protein yield and integrity was investigated by SDS-PAGE and Western Blot. Rabbit immune IgG derived by the immunization with the plastid-targeted variant ofPf GAP50 was analyzed by immune fluorescence assay (IFA) and zygote inhibition assay (ZIA).Pf GAP50 could be produced in both subcellular compartments at different yields IMAC (Immobilized Metal Affinity Chromatography) purification from extract yielded up to 4.1 μg/g recombinant protein per fresh leaf material for ER-retarded and16.2 μg/g recombinant protein per fresh leave material for plasmid targetedPf GAP50, respectively. IgG from rabbit sera generated by immunization with the recombinant protein specifically recognized different parasite stages in immunofluorescence assay. Furthermore up to 55 % inhibition in anin vitro zygote inhibition assay could be achieved usingPf GAP50-specific rabbit immune IgG. Conclusions The results of this study demonstrate that the plant-producedPf GAP50 is functional regarding the presentation of inhibitory epitopes and could be considered as component of a transmission-blocking malaria vaccine formulation.